Zerumbone-Loaded Nanostructured Lipid Carrier Induces Apoptosis of Canine Mammary Adenocarcinoma Cells. (15th October 2018) - Foong, Jia Ning; Selvarajah, Gayathri Thevi; Rasedee, Abdullah; Rahman, Heshu Sulaiman; How, Chee Wun; Beh, Chaw Yee; Teo, Guan Young; Ku, Chi Ling
Abstract : Canine mammary gland tumor (CMT) is the most common tumor in intact female dog. Zerumbone (ZER) has promising anticancer properties, but plagued with poor water solubility, poor absorption, bioavailability, and delivery to target tissues. To solubilize, ZER was loaded into nanostructured lipid carrier (NLC) to produce ZER-loaded NLC (ZER-NLC). The objectives of this study were to determine the antiproliferative effect and the mode of cell death induced by ZER-NLC and ZER on a canine mammary gland tumor (CMT) adenocarcinoma primary cell line. There was no significant difference ( p >0.05) between ZER-NLC and ZER treatments in the inhibition of CMT cell proliferation; thus, the loading of ZER into NLC did not compromise the cytotoxic effect of ZER. Microscopically, ZER-NLC- and ZER-treated CMT cells showed apoptotic cell morphology. ZER-NLC and ZER treatments significantly downregulated the antiapoptotic Bcl-2 and upregulated the proapoptotic Bax gene expressions in CMT cells. Both ZER-NLC and ZER-treated CMT cells showed significant ( p <0.0001) increases in caspase-8, -9, and -3/7 protein activities. In conclusion, ZER-NLC induced CMT cell death via regulation of Bcl-2 and Bax gene expressions and caspase activations, indicating the involvement of both the intrinsic and extrinsic pathways of apoptosis. This study provided evidences for the potential of ZER-NLC as an anticanine mammary gland adenocarcinoma chemotherapy.